Inhibition of fructose-1,6-bisphosphatase by fructose 2,6-biphosphate. - Van Schaftingen, E (1981)
Fructose 2,6-bisphosphate, a known powerful stimulator of phosphofructokinase [Van Schaftingen, E., Hue, L. & Hers, H.-G. (1980) Biochem. J. 192, 897-901] was found to inhibit, at micromolar concentrations, liver and muscle fructose-1,6-biphosphate (D-fructose-1,6-bisphosphate 1-phosphohydrolase, EC 3.1.3.11). The main characteristics of this inhibition are that (i) it is much stronger at low than at high substrate concentrations, (ii) it changes the substrate saturation curve from almost hyperbolic to sigmoidal, and (iii) it is synergistic with the inhibition by AMP. This inhibition may play an important role in the stimulation of gluconeogenesis by glucagon, because this hormone is known to decrease the concentration of fructose 2,6-bisphosphate in the liver [Van Schaftingen, E., Hue, L. & Hers, H.-G. (1980) Biochem. J. 192, 887-895].